Philip A. Cunningham, Ruth Langer, and Jesper Svartvik, Eds. Enabling Dialogue about the Land: A Resource Book for Jews and Christians - Korn, Eugene (Studies in Christian-Jewish Relations, 2021)
No abstract is available.